Reason, statecraft and the art of war: a politique reassessment. Issue 2 (3rd April 2015) - Jones,
Abstract : Recent events in world politics, from the implosion of Syria and the Ukraine to China's growing assertiveness in the East and South China Seas, have exposed the limitations of the dominant idealist and normativist paradigms in the study of international relations. In a world that is more Metternich than Rawls, it is necessary once again to examine statecraft from a realist perspective and to focus on the reasons of state that have informed its practice since the sixteenth century. Attention, here, is also focused on the rhetoric that informed political counsel and how a form of prudential reasoning shaped the art of diplomacy. In this context, casuistry, which involved applying principles of case law in particular circumstances, offered a mode of practical reasoning very different from contemporary normative approaches whose rhetoric seems increasingly divorced from the real practice of power and interest. Casuistry can be seen, as Stephen Toulmin has argued, as a form of situational or practical ethics. Casuistry, prudence and a particularist ethical practice might offer a more illuminating way of interpreting our increasingly complicated, interconnected but by no means integrated world.